IMPLEMENTASI KEBIJAKAN SATU DATA INDONESIA: TANTANGAN HUKUM DAN ADMINISTRASI PUBLIK - Loso Judijanto (CV. Adiba Aisha Amira, 2025)
The One Data Indonesia Policy is a government initiative to encourage the integration and harmonisation of data across sectors in order to improve the quality of evidence-based policy making. The implementation of this policy faces various complex legal and public administration challenges. The legal challenges include compliance with existing regulations, data protection, and privacy in accordance with international standards. Meanwhile, in terms of public administration, coordination between government agencies, both at the central and regional levels, is a major obstacle, coupled with a lack of human resources competent in the field of technology and data analysis. To overcome these obstacles, efforts are needed to strengthen institutional capacity and bureaucratic reform that is adaptive to technological developments. Only with these steps can the objective of the One Data Indonesia policy to provide accurate and reliable data be achieved, thus supporting the improvement of the quality of public policy and sustainable development.